Racial Prejudice in the Classroom: A Developmental Counselling Approach - Allan, John A. B.; Nairne, Judith E. (Canadian Journal of Counselling and Psychotherapy, 2012)
The writers were approached by an elementary school principal for help with incidences of overt racial prejudice in a regular Grade 5 class. In order to effect change it was decided to work with the whole class rather than just the identified children. To this end, the developmental counselling approach of classroom discussions was used. Four topics were selected: Being a New Canadian, Being New, Being Different and Being Racially Different. The purpose of the discussions was to strengthen self-esteem by valuing each child's unique ethnic identity before helping the children shift to understanding and accepting differ- ences. The format for each discussion session was similar. A series of detailed stimulus questions were provided to help children explore the issues, understand them, and to stimu- late positive action. The results indicated that these questions and the discussions activated positive racial attitudes and greatly improved the emotional climate of the classroom. Follow-ups one week, three months, and one year later indicated that incidences of racial prejudice did not reoccur.